PARTICIPATION OF MALIOBORO’S PARKING ATTENDANTS RELOCATION IN RIGHT TO THE CITY PERSPECTIVE - Pinurba Parama Pratiyudha (Jurnal Pengembangan Kota, 2020)
Right to the city become one of essential point in New Urban Agenda discussion, as the adoption of Sustainable Development Goals which includes point 11 on Sustainable Cities and Human Settlements. Right to the city is a concept which encloses political power, land ownership, and social justice within globalized cities which run into rapid change. Lefebvre describes the right to the city as people cry and demand a transformed and renewed urban life. Participation is seen as a basic right in the concept of the right to the city. This article drawing on a study case of relocation of Malioboro’s parking attendants. The relocation itself was one of the policies to revitalize tourism area along Malioboro street. In the process, there are some resistances from Malioboro’s parking attendants emerge as their concern on their sustainability after the relocation into the new place. Based on the field research, this article concludes that the process of participation that occurs does not meet up with parking attendants aspiration and the process is ruined by the government. Public participation is ineffective at the process and ruined as the government intervention in Malioboro parking attendants organization. The ineffectiveness of public participation is due to the logic of technocratic participation and the government's informal approach to some parking attendants.